When do family firms consider issuing external equity? Understanding the contingent role of families' need for control. Issue 3 (2nd September 2019) - Kupp, Martin; Schmitz, Bianca; Habel, Johannes
Abstract : Purpose: Prior research has argued that family firms are reluctant to consider external equity as a source of financing because they fear a loss of control, which would limit their socioemotional wealth. However, prior empirical research has neglected potential contingencies that determine whether family firms' need for control affects their equity financing decisions. The purpose of this paper is to provide first insight into this research void. Design/methodology/approach: The paper builds on rational choice theory and a logit regression using secondary data. Findings: The study shows that the effect of family firm owners' need for control on their consideration of external equity depends on the extent to which owners expect investors to interfere with management and the extent to which decision making is affected by emotions. Hereby, the present study provides evidence that family firm owners' decisions to use external equity are more complex than previously presumed. Research limitations/implications: This study has several limitations that provide fruitful avenues for further research. Overall, the authors list and detail seven different limitations in the paper, e.g. the narrow focus on equity financing, the use of a partial model, the fact that the authors did not conceptualize differences between different types of investors (such as high net worth individuals, private equity firms and venture capital firms) in the model and further more. Practical implications: The study shows that investors need to understand the complex interplay among family firms' need for control, expected investor interference and emotional decision making, to correctly assess their chances of success when approaching family firms for equity. Originality/value: Prior empirical research has neglected potential contingencies that determine whether family firms' need for control affects their equity financing decisions. The present paper provides first insight into this research void.